The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12149-014-0902-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of SUV-based parameters derived from pre-treatment 18F-FLT PET/CT for short-term outcome with head and neck cancers

Abstract: Pre-treatment MTV is the most useful parameter with FLT PET/CT. TLP and SUVpeak may also provide important prognostic information for patients with HNSCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…SUV peak has been proposed to overcome the shortcoming of SUV max , defined as the average SUV within a small, fixed size region of interest centered on a high uptake part of the tumor (18). SUV peak has been reported (11,19,20) to be prognostic in several types of malignancy. In patients with osteosarcoma, we revealed that SUV peak at the posttherapy scan is an independent prognostic factor for OS.…”
Section: Discussionmentioning
confidence: 99%
“…SUV peak has been proposed to overcome the shortcoming of SUV max , defined as the average SUV within a small, fixed size region of interest centered on a high uptake part of the tumor (18). SUV peak has been reported (11,19,20) to be prognostic in several types of malignancy. In patients with osteosarcoma, we revealed that SUV peak at the posttherapy scan is an independent prognostic factor for OS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by some of the previous studies. In a study of 32 patients with HNSCC, Hoshikawa et al showed that metabolic tumor volume and total lesion proliferation based on pretreatment FLT-PET were significantly associated with locoregional control and overall survival, while SUV max played no prognostic role 28 . In another study of 26 high-grade glioma patients, Idema et al showed that both FLT-derived proliferative volumes adapted by the signal-to-background ratio (PV SBR ) and SUV max were predictive of OS in univariate analysis, but only PV SBR remained statistically significant in multivariate analysis 35 .…”
Section: Discussionmentioning
confidence: 99%
“…42 There is an increasing assortment of radiotracers targeting alternate pathways (fluorothymidine F 18, cellular proliferation), receptor targets, and tumor environmental conditions (fluoromisonidazole F 18, tumor hypoxia) that may prove useful for further characterizing HNSCC in patients. [43][44][45]…”
Section: Prognostic Evaluation With Functional Imagingmentioning
confidence: 99%